To be (routine) or not to be (routine), that is the question: a cross-country task-based answer. (16th August 2018) - Marcolin, Luca; Miroudot, Sébastien; Squicciarini, Mariagrazia
Abstract: This work proposes a new measure of the routine content of occupations and sectors for 20 OECD countries, based on information about the sequence and flexibility of the tasks performed on the job. A negative but weak association emerges between routineness and skill intensity, which suggests the importance of both technological and organizational considerations in the measure of routine intensity. Between 2000 and 2010, employment mainly grew in non-routine occupations, especially in market services, while manufacturing shed routine and non-routine jobs. Changes in shares of employment by routine quartile are dominated by within-effects.